Komuniksasi Pelayanan Publik Kepolisian Polda Banten Melalui Program Training of Trainer (ToT) - Saifulloh, Muhammad; Manogari, Rialdo Rezeky; Prihatiningsih, Nunuk (Jurnal Pustaka Dianmas, 2022)
The implementation of public services is an effort by the state to meet the basic needs and civil rights of every citizen to goods, services, and administrative services provided by public service providers. Likewise, the Indonesian National Police, especially the Banten Regional Police, communicates to provide public services. Through public services, the presence of state institutions can be felt by the community with various forms of communication adapted to the existence of the police itself. To provide input on how the Banten Regional Police communicates, it is necessary to make various efforts so that public services can be improved and improved. One of the methods that is trying to be done in response to findings in various studies that have been carried out related to public services in Indonesia is to carry out Community Service in the form of discussions and knowledge dissemination entitled "Communication of the Banten Regional Police through Public Service". The aim is to improve communication and improve services from various parties both at the Polda level to the Polsek level throughout the Banten region, this activity is carried out by holding a Training of Trainers (ToT) and exposure related to the importance of communication and participation of police members. Evaluation of the implementation of activities is carried out by means of lectures and discussions on materials related to communication and public services.